Optimal Contracts in a Continuous-Time Delegated Portfolio Management Problem - Ouyang, Hongbing (Review of Financial Studies, 2002)
This article studies the contracting problem between an individual investor and a professional portfolio manager in a continuous-time principal-agent framework. Optimal contracts are obtained in closed form. These contracts are of a symmetric form and suggest that a portfolio manager should receive a fixed fee, a fraction of the total assets under management, plus a bonus or a penalty depending upon the portfolio's excess return relative to a benchmark portfolio. The appropriate benchmark portfolio is an active index that contains risky assets where the number of shares invested in each asset can vary over time, rather than a passive index in which the number of shares invested in each asset remains constant over time.